Oracle database 10g : the complete reference. - Loney, Kevin, ....- (New York : McGraw-Hill, 2004)
Get a thorough understanding of Oracle Database 10g from the most comprehensive Oracle database reference on the market, published by Oracle Press. From critical architecture concepts to advanced object-oriented concepts, this powerhouse contains nearly 50 chapters designed to enlighten you. Upgrade from earlier versions, use SQL, SQL Plus, and PL/SQL. Get code examples and access popular documentation PDFs plus a full electronic copy of the book on the included CD-ROM. Go beyond the basics and learn security, text searches, external tables, using Java in Oracle, and a great deal more.
Keywords: Database systemen